Emotional Regulation and Impulsive in Fashion Purchases among Emerging Adulthood: An In-Depth Quantitative Study - Putri, Dinda Maulina; Marniati, Marniati; Purnomo, Reza Asep Adi (Universitas Negeri Surabaya, 2025)
Background: Emerging adulthood is characterized by self-image exploration and emotional instability, where insufficient emotion regulation may result in impulsive fashion purchases, highlighting a significant issue in this developmental phase. Objective: This research is to analyze emotion regulation and impulsive buying in fashion purchases in emerging adulthood. Method: The purposive sampling technique was used with 107 respondents, using emotion regulation scale and Impulsive Buying Tendency Scale to statistic test. The analysis was conducted using JASP version 0.19.3.0 with linear regression technique, moderation, and independent samples t-test at 5% significance level. Results: Emotional regulation has a negative effect with a value of (β = -0.267) on impulsive buying, and emotional regulation has a statistically significant difference on gender with a value of (p = 0.013), while impulsive buying has no different value on gender with a value of (p = 0.717). Finally, the value of (B = -0.543, p = 0.033) on gender moderation was obtained. Conclusion: The conclusion is that emotional regulation can reduce impulsive buying, with the same level of impulsivity between genders. Abstrak Latar Belakang: Emerging adulthood adalah masa yang penuh gejolak dan pencarian citra diri. Terkadang mereka tidak mampu meregulasi emosinya saat emosinya memburuk, sehingga memunculkan perilaku impulsive dalam pembelian busana. Tujuan: Penelitian ini untuk menganalisis regulasi emosi dan pembelian impulsive dalam pembelian busana pada emerging adulthood. Metode: Penelitian ini menggunakan purposive sampling. Data dikumpulkan dari 107 responden menggunakan skala regulasi emosi adaptasi Indonesian Emotion Regulation Questionnaire for Sport (IERQ4S) dan skala pembelian impulsif adaptasi dari Impulsive Buying Tendency Scale. Analisis dilakukan menggunakan JASP versi 0.19.3.0 dengan teknik regresi linier, uji moderasi, dan independent samples t-test pada taraf signifikansi 5%. Hasil: Berdasarkan uji statisik, regulasi emosi berpengaruh negatif dengan nilai (β = -0.267) terhadap impulsive buying. Selain itu, regulasi emosi memiliki nilai beda pada gender dengan nilai (p = 0.013), sedangkan impulsive buying tidak memiliki nilai beda pada gender dengan nilai (p = 0.717). Terakhir, didapatkan nilai (B = -0.543, p = 0.033) pada moderasi gender. Simpulan: Kesimpulannya regulasi emosi mampu menurunkan impulsive buying, dengan tingkat impulsive sama antar gender.